Pengaruh Risiko Pembiayaan, Kecukupan Modal, Dana Pihak Ketiga dan Efisiensi Operasional Terhadap Profitabilitas Bank Syariah di Indonesia - Sagab Baitullah; Rahmah, St; Muslimah (STIT Al-Quraniyah Manna, 2020)
This study aimed to examine the influence of financing risk, capital adequacy,and third party funds to profitability of Islamic banks in Indonesia. The population of this study is Islamic Banks listed on the Indonesia Stock Exchange 2012-2016 period. The sampel is 8 of 5 years. Data obtained by the method of purposive sampling. Research hypotesis were tasted using multiple linear regresion method.The results of this study using risk financing no significant effect on profitability, capital adequacy significant effect on profitability, the third party fund had no significant effect on profitability and operational efficiency significant effect on profitabilitas. Keywords:financing risk, capital adequacy, third-party funds, operationl efficiency, profitability Islamic banks